LTE E-MBMS capacity and inter-site gains - Correia, A. (2018)
Introduction The Third Generation Partnership Project (3GPP) has launched the study item evolved UMTS terrestrial radio access (UTRA) and UMTS terrestrial radio access network (UTRAN), which studies the means to achieve further substantial leaps in terms of service provisioning and cost reduction. The overall target of the long-term evolution (LTE) of 3G was to arrive at an evolved radio access technology that can provide service performance on parity with current fixed-line access. As it is generally assumed that there will be a convergence toward the use of Internet protocol (IP)- based protocols (i.e., all services in the future will be carried on top of IP), the focus of this evolution was on enhancements for packet-based services. 3GPP concluded the Release 8 of the evolved 3G radio access technology in 2008, with subsequent initial deployment in the 2009-2010 time frame. At this point, it is important to emphasize that this evolved RAN is an evolution of the current 3G networks, building on already made investments. The 3GPP community has been working on LTE, and various contributions were made to implement evolved MBMS in LTE [1].